A coordinatively saturated cobalt complex as a new kind catalyst for efficient electro- and photo-catalytic hydrogen production in purely aqueous media. (29th June 2017) - Peng, Qiu-Xia; Xue, Dan; Yang, Ling-Fen; Zhan, Shu-Zhong
Abstract: It has been shown that coordinatively unsaturated complexes can catalyze hydrogen production via an unstable hydride intermediate. Herein we present a new kind of water soluble catalyst based on a coordinatively saturated cobalt complex, [(phen)2 Co(CN)2 ]⋅ClO4 1 that is formed by the reaction of 1, 10-phenanthroline (phen), Co(ClO4 )2 ·6H2 O and tetracyanoethylene (TCNE). Under photoirradiation with blue light ( λ max  = 469 nm) in air, together with [Ru(bpy)3 ]Cl2 and ascorbic acid in a pH 5.5 aqueous solution, 1 possesses photocatalytic activity for water reduction to hydrogen with an initial turnover number (TON) of 1232H2 per mol of catalyst at first 10 h, and this activity is sustained for at least 70 h. This can be attributed to that oxidative quenching by1 (kq  = 1.69 × 10 10  M −1  s −1 ) dominates over reductive quenching to [Ru(bpy)3 ]Cl2 by ascorbic acid (kq  = 1.55 × 10 10  M −1  s −1 ). Additionally, 1 electrocatalyze hydrogen generation from a neutral water with a turnover frequency (TOF) of 1113.1 mol of hydrogen per mole of catalyst per hour (mol H2 /mol catalysts/h) at an overpotential (OP) of 838 mV. We hope this can afford a new method in proton or water reduction catalysis using coordinatively saturated complexes in purely aqueous media. Graphical abstract: Highlights: A coordinatively saturated complex [(phen)2 Co(CN)2 ]·ClO4 1 is formed by the reaction of phen, Co(ClO4 )2 and TCNE. 1 electrocatalyzes H2 evolution from a neutral water with a TOF of 1113.1 mol H2 /mol catalysts/h at an OP of 837.6 mV. 1 produces hydrogen with an initial turnover number (TON) of 1232 H2 per mol of catalyst at first 10 h. Oxidative quenching by1 dominates over reductive quenching to [Ru(bpy)3 ]Cl2 by ascorbic acid.